An econometric analysis of capability enhancement effects of microfinance among women in Tsholotsho District, Zimbabwe. - Matindike, Shadreck (Midlands State University, 2022)
There has been an unprecedented effort to reduce poverty in the world recently and the achievements have been significant. Various definitions regarding nature as well as the scope of poverty exist. Indeed, it is evident that the entirety of the history of poverty studies so far is a history of different definitions. However, there is a general agreement towards the conclusion that poverty is the deficiency of capabilities to achieve fundamental functioning. It has been observed that the burden of poverty is still higher on women than it is on men, a phenomenon termed 'feminisation of poverty' and studies on ways to enhance women's capabilities are gaining more attention like never before. Microfinance is one of the tools proposed for enhancing capabilities through mixed results on its efficacy exist in the literature. Tsholotsho, the district with higher feminisation in the most deprived province of Zimbabwe, provides a fertile ground to investigate the impact of microfinance on capability enhancement among women. The focal objectives were to identify analyse the capability enhancement effects of microfinance through microenterprise development and women empowerment in Tsholotsho District, Zimbabwe. It is out of the Capability Approach by Amarty Sen that this study derived its primary proposition -that evaluation of microfinance effects must be done in the context of capability enhancement. In an endeavour to avoid boondoggle research in favour of an avant-garde study, some trappings from sociology are evident - the roles of birth order effects and family business history effects on capability enhancement were analysed. Rooted on the one true reality independent from the researcher ontology, an epistemology that assumed observable and quantifiable facts, an objective standing as the axiology, in line with the positivism paradigm, the researcher employed quantitative analysis. Three models were formulated, namely, microfinance participation and ii microenterprise development based on logit regression while women empowerment model premised on Tobit regression. Findings show that individuals with diversified income sources and high spouse incomes are less likely to adopt microfinance while those with a family business background and large cattle herd size are more likely to participate. Age and membership in other social groups are insignificant in determining adoption of microfinance among women. The study shows that microfinance enhances the capabilities of women through microenterprises development. Birth order effects and family business background contribute positively to microenterprise development. Perceived impact of microfinance on women empowerment is influenced positively by birth order effects and family business background. The majority of the members of microfinance projects investigated scored highly the positive perceived impact of microfinance on women empowerment based on functionings representing various latent capabilities. Overall, microfinance was found to be a tool that can enhance capabilities in the context of capabilities approach as it enhances women empowerment and women micro entrepreneurship. The study recommends packaging of microfinance taking into account birth order and family business history effects in Tsholotsho and also spreading of informal microfinance models to other districts and provinces. The study identified areas which require further study, namely, (i) conducting a replica of this study in other districts with similar socio economic situations to confirm the research findings of this study; (ii) carrying out a study, looking at a larger number of variables excluded in the current study can help in reducing rural poverty; and (iii) assessing the economic impacts of male folk migration to South Africa on women empowerment and general poverty alleviation in rural areas, especially Tsholotsho.